Studies on pore blocking mechanism and technical feasibility of a hybrid PAC-MF process for reclamation of irrigation water from biotreated POME - Amosa, Mutiu Kolade; Jami, Mohammed Saedi; Al-Khatib, Ma An Fahmi Rashid; Majozi, Thokozani (Taylor & Francis Group, LLC, 2016)
An integrated low-cost adsorption (with powdered activated carbon) and cross-flow membrane filtration (with microfiltration membranes of 0.1 and 0.2 μm pore sizes) process was employed for the treatment of biotreated POME to produce irrigation water fully benchmarked with water-quality standards. The permeate quality was within the recommended standard for irrigation water as the concentrations of all critical constituents were well below their recommended values. Sustainability of the process integration was further confirmed with the domination of cake filtration over other blocking mechanisms with higher R2 values at all trans-membrane pressures. Suitable extended usage of permeate was found for toilet/urinal flushing.